HUBUNGAN ANTARA PENYESUAIAN DIRI DAN STRES AKADEMIK PADA MAHASISWA BARU FAKULTAS PSIKOLOGI DI UNIVERSITAS KRISTEN SATYA WACANA - Marna Filhia Tuwanakotta,; Wahyuni Kristinawati, (Journal of Innovation Research and Knowledge, 2024)
This research aims to determine the relationship between adjustment and academic stress in new students at the Faculty of Psychology, Satya Wacana Christian University. This research was conducted on 308 students using a correlational quantitative approach. Data were obtained using the adjustment scale The Adaptation To Student College Questionnaire (SACQ) (Baker and Siryk, 1989) and the Student-Life Stress Inventory academic stress scale developed by Gadzella (2005). The results of the correlational test were carried out using Product Moment correlation and obtained a correlation coefficient of -0.380 with a sig value. = 0.000 (p<0.01), which means there is a negative relationship between adjustment and academic stress in new students at the UKSW Faculty of Psychology